(3GdCTQGa aj efGRd GdCTQGas - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s
(3ChdgG (B:s
(3MOKfG CHh GdMSf CMeO Hf eMeO Hf YeQ bGd MOKfG GHh HcQ ef cJGHg bGd MOKfG GHQGgje Hf GdefPQ GdNRGei s
(3BNQgG (B:s
(3bGd (B: (3aNQLJ ef YfOg hCfG ef CZfi GdfGS hHYOg BNQ cJGH GdCTQGa s
(3GdfSNI eUhQI ef fSNI dCMO GdYdeGAs
(3ef QhGjI CHj GdMSf CMeO Hf eMeO Hf GdGUHgGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B19 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs